Utilizing Digital Platforms for Diplomacy in ASEAN: A Preliminary Overview - Anak Agung Mia Intentilia; Putri Ekaresty Haes; Gede Suardana (COMMUSTY Journal of Communication Studies and Society, 2022)
This paper is a preliminary overview that aims to seek the general answer of who are the state and non-state actors involved in ASEAN digital diplomacy. By using the theory of network diplomacy and the concept of digital diplomacy, this paper outlines official websites and social media accounts related to ASEAN. The methodology uses in this paper is descriptive qualitative with secondary data. This paper finds that ASEAN acts as a state actor to conduct digital diplomacy by utilizing digital platforms through the ASEAN official website and social media accounts on Twitter, Facebook, and Instagram. The contents of ASEAN official accounts cover the internal and external cooperation as part of its network diplomacy. Moreover, youth organization, think tank, and educational institution are part of the non-state actors discussed in this paper. These non-state actors also actively participated in disseminating information regarding ASEAN internal and external issues. Therefore, both state and non-state actors related to ASEAN have utilized digital platforms to communicate with the public and support the maintenance of ASEAN network diplomacy.